(untitled) (Scientific journal of the Fergana State University, 2024)
The article systematizes and summarizes historiographic material - studies of foreign English-speaking authors on the history of Bukhara Emirate in the XIX century. A brief characteristic of the works of Western English-speaking authors and the periodization of foreign English literature on the history of the Emirate are presented.